Helping Clients Uncover Metaphoric Understandings of Bulimia - Cummings, Anne L. (Canadian Journal of Counselling and Psychotherapy, 2007)
The written post-session responses of three women with bulimia were analyzed qualitatively for instances of metaphoric understanding of their difficulties with food during 20 to 24 sessions of therapy. Results showed a gradual deepening of the metaphoric understanding of what the troubled eating representee for each client. Metaphoric understandings include dealing as a way of dealing with family, nurturing self, swallowing feelings, coping with societal pressures, and distancing other people.